Holocene development and climatic sensitivity of an Amazonian peatland pole forest: Nueva York, Peru - Christine M. Åkesson; Katherine H. Roucoux; Arnoud Boom; Greta C. Dargie; Jhon del Aguila-Pasquel; Gerardo Flores; Pauline Gulliver; William Hiles; Timothy R. Baker; Frederick C. Draper; Adam Hastie; Eurídice N. Honorio Coronado; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Monitoring water level dynamics in neotropical peatlands with earth observation data - Antje Uhde; Laura L. Hess; Alison M. Hoyt; Christiane Schmullius; Euridice N. Honorio Coronado; Edmundo Mendoza Olmos; Gerardo Flores Llampazo; Susan Trumbore; Timothy Baker; Juan S. Hernandez Suarez; Oliver L. Phillips; Frederick C. Draper; et al. (Remote Sensing of Environment, 2026)

Sustainable management of non-timber forest products in Peruvian Amazonia: lessons learnt from participatory use of smartphone technology - Charlotte E. Wheeler; Althea L. Davies; Luis Andueza; Lydia E.S. Cole; Nállarett Dávila; Jhon Del Águila; Margarita del Aguila Villacorta; Frederick C. Draper; Charlotte L.D. Evans; Eurídice N. Honorio Coronado; Nina Laurie; Eva Loja; et al. (Journal of Environmental Management, 2025)

Understanding different dominance patterns in western Amazonian forests - Laura Matas‐Granados; Frederick C. Draper; Luis Cayuela; Julia G. de Aledo; Gabriel Arellano; Celina Ben Saadi; Timothy R. Baker; Oliver L. Phillips; Eurídice N. Honorio Coronado; Kalle Ruokolainen; Roosevelt García‐Villacorta; Katherine H. Roucoux; et al. (Ecology Letters, 2024)
Dominance of neotropical tree communities by a few species is widely documented, but dominant trees show a variety of distributional patterns still poorly understood. Here, we used 503 forest inventory plots (93,719 individuals ≥2.5 cm diameter, 2609 species) to explore the relationships between local abundance, regional frequency and spatial aggregation of dominant species in four main habitat types in western Amazonia. Although the abundance‐occupancy relationship is positive for the full dataset, we found that among dominant Amazonian tree species, there is a strong negative relationship between local abundance and regional frequency and/or spatial aggregation across habitat types. Our findings suggest an ecological trade‐off whereby dominant species can be locally abundant ( local dominants ) or regionally widespread ( widespread dominants ), but rarely both ( oligarchs ). Given the importance of dominant species as drivers of diversity and ecosystem functioning, unravelling different dominance patterns is a research priority to direct conservation efforts in Amazonian forests.

Dominant tree species drive beta diversity patterns in western Amazonia - Frederick C. Draper; Gregory P. Asner; Eurídice N. Honorio Coronado; Timothy R. Baker; Roosevelt García‐Villacorta; Nigel C. A. Pitman; Paul V. A. Fine; Oliver L. Phillips; Ricardo Zárate Gómez; Carlos A. Amasifuén Guerra; Manuel Flores Arévalo; Rodolfo Vásquez Martínez; et al. (Ecology, 2019)
The forests of western Amazonia are among the most diverse tree communities on Earth, yet this exceptional diversity is distributed highly unevenly within and among communities. In particular, a small number of dominant species account for the majority of individuals, whereas the large majority of species are locally and regionally extremely scarce. By definition, dominant species contribute little to local species richness (alpha diversity), yet the importance of dominant species in structuring patterns of spatial floristic turnover (beta diversity) has not been investigated. Here, using a network of 207 forest inventory plots, we explore the role of dominant species in determining regional patterns of beta diversity (community‐level floristic turnover and distance‐decay relationships) across a range of habitat types in northern lowland Peru. Of the 2,031 recorded species in our data set, only 99 of them accounted for 50% of individuals. Using these 99 species, it was possible to reconstruct the overall features of regional beta diversity patterns, including the location and dispersion of habitat types in multivariate space, and distance‐decay relationships. In fact, our analysis demonstrated that regional patterns of beta diversity were better maintained by the 99 dominant species than by the 1,932 others, whether quantified using species‐abundance data or species presence–absence data. Our results reveal that dominant species are normally common only in a single forest type. Therefore, dominant species play a key role in structuring western Amazonian tree communities, which in turn has important implications, both practically for designing effective protected areas, and more generally for understanding the determinants of beta diversity patterns.